Environmental geochemistry site characterization, data analysis and case histories - De Vivo, B. (Benedetto); Belkin, H. E.; Lima, Annamaria (Elsevier, 2018)
Environmental Geochemistry: Site Characterization, Data Analysis and Case Histories, Second Edition, reviews the role of geochemistry in the environment and details state-of-the-art applications of these principles in the field, specifically in pollution and remediation situations. Chapters cover both philosophy and procedures, as well as applications, in an array of issues in environmental geochemistry including health problems related to environment pollution, waste disposal and data base management. This updated edition also includes illustrations of specific case histories of site characterization and remediation of brownfield sites.--Provided by publisher.